Bunga Bank (Riba) Dalam Pandangan Hukum Islam - Veri Mei Hafnizal (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2017)
In the modern economy, banks are intermediaries, and channeling of funds between the parties surplus with the underfunded. The purpose of writing this paper was to determine the bank interest under Islamic law. This research was conducted through a normative juridical research methods or research literature. The proposition which forbids the interest contained in the Qur'an Surat Ar-Rum verse 39, an-Nisa verse 160-161, Ali-Imran verse 130, al-Baqarah verse 275-279. Hadith of the Prophet one "Prophet condemned interest, his deputy and the author, as well as two witnesses, and he said they were equally condemned." (HR.Muslim). Scholars have agreed that the bank interest is riba and is haraam, such as cleric Abu zahrah, Abu 'ala al-Maududi Abdullah al-Arabi and Yusuf Qaradawi and issued a Fatwa about its forbidden.